Hemolytic disease of the fetus and newborn caused by irregular antibody: A mortality case report and case series during the past 15 years in NCKUH - Ming-Ta Chuang; Chiung-Hsin Chang (Taiwanese Journal of Obstetrics & Gynecology, 2022)
Objective: Hemolytic disease of the fetus and newborn (HDFN) caused by irregular antibodies is a rare, but possibly life-threatening condition. We report a case of severe intrauterine hemolysis caused by anti-E alloimmunization, and review 16 cases in the past 15 years of our hospital. Case report: A woman with gestational age 28 weeks and 5 days, received emergent Cesarean section because of fetal distress. The baby was expired at the next day after delivery and the comprehensive study showed severe anemia and alloimmunization related hemolysis caused by anti-E due to high antibody titer (1: 4096). Conclusion: Anti-E antibody is one of the most common non-Rhesus D antibodies in the pathogenesis of HDFN, but rarely leads to severe hemolysis. However, our case has the highest reported anti-E titer in HDFN and is the first case of mortality during the past 15 years in NCKUH.